In vivo assessment of antioxidant, antigenotoxic, and antimutagenic effects of bark ethanolic extract from Spondias purpurea L - Brito, Lorrane Davi; Araujo, Caroline de Souza; Cavalcante, Dalita Gomes Silva Moraes [UNESP]; Gomes, Andressa Silva [UNESP]; Zocoler, Marcos Alberto; Yoshihara, Eidi; Job, Aldo Eloizo [UNESP]; Kerche, Leandra Ernst (Taylor & Francis, 2022)
Medicinal plants have always been used for therapeutic purposes; however, some plants may contain toxic and mutagenic substances. The aim of this study was to assess the cytotoxic, genotoxic, mutagenic, antioxidant, antigenotoxic, and antimutagenic effects of the bark ethanolic extract of Spondias purpurea L. using male and female Swiss albino mice. To determine the protective effects of the extract, benzo[a]pyrene (B[a]P) and cyclophosphamide (CP) were selected as cell damage inducers. The extract was examined at doses of 500, 1000, or 1500 mg/kg body weight (BW)via gavage alone or concomitant with B[a]P or CP. Oxidative stress was measured by quantification of blood catalase activity (CAT), reduced glutathione (GSH) levels in total blood, liver, and kidney, and concentrations of malondiadehyde (MDA) in liver and kidney. Genotoxicity and antigenotoxicity were evaluated by the comet assay using peripheral blood. Cytotoxicity, mutagenicity, and antimutagenicity were determined utilizing the micronucleus test in bone marrow and peripheral blood. The S. purpurea L extract increased CAT activity and GSH levels accompanied by a decrease in MDA levels after treatment with B[a]P and CP. No genotoxic, cytotoxic, or mutagenic effects were found in mice exposed only to the extract. These results indicate that the extract of S. purpurea exhibited protective effects against oxidative and DNA damage induced by B[a]P and CP.
Keywords: comet assay; micronucleus test; oxidative stress; plant extract; Spondias purpurea